2021
DOI: 10.1007/s41779-021-00610-4
|View full text |Cite
|
Sign up to set email alerts
|

Control of the setting reaction and strength development of slag-blended volcanic ash-based phosphate geopolymer with the addition of boric acid

Abstract: This work aimed to evaluate the role of the addition of blast furnace slag for the formation of reaction products and the strength development of volcanic ash-based phosphate geopolymer. Volcanic ash was replaced by 4 and 6 wt% of ground granulated blast furnace slag to accelerate the reaction kinetics. Then, the influence of boric acid for controlling the setting and kinetics reactions was also evaluated. The results demonstrated that the competition between the dissolution of boric acid and volcanic ash-slag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…31 Therefore, though the curing temperature is interesting for accelerating the reaction rate, the rapid formation of the gels at an early age inhibits further reaction progress with time, which also limits the compressive strength increases at a late age. 32 This is also true for the acid aluminum phosphate activated volcanic ash, where the speeding up of the precipitation condensation reaction in the formation of the gels makes useless additional heat treatment for the strength development. Those minerals are the same that were initially present in volcanic ash.…”
Section: Relationship Between Reaction Progress and Strength Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Therefore, though the curing temperature is interesting for accelerating the reaction rate, the rapid formation of the gels at an early age inhibits further reaction progress with time, which also limits the compressive strength increases at a late age. 32 This is also true for the acid aluminum phosphate activated volcanic ash, where the speeding up of the precipitation condensation reaction in the formation of the gels makes useless additional heat treatment for the strength development. Those minerals are the same that were initially present in volcanic ash.…”
Section: Relationship Between Reaction Progress and Strength Developmentmentioning
confidence: 99%
“…was benecial only for improving compressive strength at an early age. 28,32 Since, the control phosphate binder without setting accelerators developed better strength at a late age. That is because the limited dissolution of the ferro/aluminosilicate was recorded due to the lowering of the acidity attributed to the acid-base reaction that occurred at the beginning of the reaction.…”
Section: The Reaction Mechanism and The Inuence Of Different Synthes...mentioning
confidence: 99%
“…Although fly ash can provide rich calcium to improve the early strength of geopolymers, long-term studies have found that calcium phosphate formed by the reaction will gradually transform into needle-like and flaky particles, which affects the long-term strength of geopolymers [ 34 , 40 ]. In addition, other studies found that the addition of solid wastes such as blast furnace slag and electrolytic manganese slag can accelerate the geopolymerization reaction, and the prepared geopolymer samples have an excellent water resistance and a high temperature resistance [ 36 , 37 ]. The disadvantages of solid wastes are that their compositions are complex and volatile, and they are rich in harmful heavy metal ions and other pollutants, such as dioxin.…”
Section: The Preparation Process Of Asp Geopolymersmentioning
confidence: 99%
“…Further work reported that adding up to 4 wt.% of slag accelerates the reaction kinetics. 23 However, the nature and the chemistry of the binder are still not well understood. Moreover, due to the complexity of the chemical composition of volcanic ash because of the presence of Ca, Mg, and Fe, the optimum mix design in terms of the molar ratios Ca/P, Mg/P, Al/P, and Fe/P that provides the best properties needs to be established.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have helped to understand that calcium and magnesium are responsible for the fast setting of volcanic ash phosphate geopolymer at room temperature, while aluminum and iron are responsible for compressive strength development. Further work reported that adding up to 4 wt.% of slag accelerates the reaction kinetics 23 . However, the nature and the chemistry of the binder are still not well understood.…”
Section: Introductionmentioning
confidence: 99%